Chemically bonded PA‐PTFE‐oil compounds by reactive processing: Chemical, thermal, morphological, and mechanical analysis. Issue 46 (18th August 2022) - Nguyen, Thanh Duong; Schmidt, Thomas; Meißner, Till; Malanin, Mikhail; Uhlig, Kai; Schlendstedt, Kornelia; Schwarz, Simona; Stommel, Markus; Voit, Brigitte; Gedan‐Smolka, Michaela
Abstract: In this research, the novel materials based on polyamide (PA), polytetrafluoroethylene (PTFE), and olefinic oil molecules are produced as a solid lubricant in metal‐plastic sliding contacts or sacrificial elements in metal–metal sliding contacts. For these applications, high durability of the compound material combined with low wear is required for long‐term use under high friction and mechanical loads. Earlier studies of IPF have shown that chemical bonding between the polymer matrix and the solid lubricant is mandatory to meet these requirements. For this purpose, the compounds are fabricated by a novel two‐step reactive processing procedure based on radiation‐modified PTFE, which exhibits reactive‐functional groups (COOH) and persistent perfluoroalkyl‐(peroxy)‐radicals (COO·). The PA‐PTFE‐oil‐cb compound materials (cb: chemically bonded) are analyzed by differential scanning calorimetry (DSC) concerning breaking down behavior and Fourier‐transform infrared spectroscopy with regards to the chemical covalent bonding state between the three components. Results of scanning electron microscopy investigations in correlation with DSC show that chemical bonding between PA and PTFE‐oil‐cb leads to a homogeneous distribution of solid lubricant particles in the three various PA matrices. Due to the chemical coupling, the compounds offer almost comparable or improved mechanical properties in the case of toughness compared to non‐modified PA. Abstract : This project's scope is the development of novel chemically bonded tribomaterials based on polyamides (PAs), irradiated polytetrafluoroethylene (PTFE), and oil molecules. The materials are processed by a two‐step of reactive‐extrusion. This article presents the compound's morphology, crystallization behavior, and mechanical properties. It was found that PA12‐(Z7321) offered the best coupling degree and is the best suitable matrix polymer for chemical coupling PA‐PTFE‐oil.